Genetic variations of Malaysian and golden thai strains of climbing perch and their hybrids based on the partial mitochondrial cytochrome oxidase subunit 1 gene - Dasuki, Awawu; Yuzine Esa,; Christianus, Annie; Mohammad Fadhil Syukri Ismail, (Penerbit Universiti Kebangsaan Malaysia, 2023)
Rapid genetic improvements from selective breeding are anticipated in many aquaculture species and mitogenome is used to complement the morphological taxonomy of hybrids to evaluate its genetic structures. A study of the genetic variations within the two strains (Malaysian strain and Golden Thai strain) of Anabas testudineus (Bloch, 1792) and their hybrids, phylogenetic trees based on cytochrome oxidase subunit 1 (CO1) of the partial mitochondrial DNA gene were constructed using Maximum Likelihood and Neighbor Joining approaches. The findings support the monophyletic status of the genus with only one haplogroup from which other haplotypes were descended and of a single common ancestor. The individual fishes’ phylogenetic relationships revealed two major clades and Saurida undosquamis as an outgroup. All the groups had high haplotype diversity, except for the hybrid Malaysian strain × golden Thai strain (0.1540±0.126). This suggests that different fish species in each of these studies had different nucleotide compositions in their mitochondrial genomes. The highest number of haplotypes and the presence of distinct haplotypes in the Golden Thai strain × Malaysian strain hybrid point to the absence of recent or regular gene flow as well as high genetic diversity within the hybrids. This study demonstrated that the mtDNA diversity of Anabas testudineus from Malaysia and Thailand had been preserved. Studies on the population genetic diversity and molecular evolution of anabas fish species can benefit from the data provided by this work.